Design, Installation and Experimentation of a Photovoltaic Station Connected to the Electricity Grid on the Campus of the University of Oujda (Morocco) - Lamkaddem, A.; Moussaoui, N. El; Rhiat, M.; Kassmi , K.; Malek, R. (Current Overview on Science and Technology Research Vol. 5, 2022)
The objective of this chapter is the study and sizing of a photovoltaic (PV) installation hooked up to the electrical network, with the aim of reducing the electricity bill of the university campus of the technopole of Oujda (Morocco). We present the dimensioning (under the PVsyst software) and the operation of a 10 kW photovoltaic station hooked up to the electrical network to supply the three-phase loads. The experimental results of measurements in the field show that the 10 kWp installation connected to the network (50 Hz, 230 V, 16 A) primarily supplies the three-phase loads, then the surplus is injected into the electrical grid. The average values of the voltages measured on the phases (T, S, R) are of the order of 238V, the currents of the phases (T, R, S) vary between 7A and 14A, and the voltages linked to the phases (SR, ST, TR) output voltages are around 418V. All the measurements obtained are in excellent agreement with the specifications and the simulations of the two installations on the PVsyst software. The Oujda university campus is entirely powered by photovoltaic renewable energy. Currently, we follow the production, consumption of electrical energy, injection into the network, and the cost of the electricity bill.